2020
DOI: 10.1002/nau.24494
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic change of the anteroposterior diameter of the levator hiatus under Valsalva maneuver at term and labor outcome

Abstract: The aim of the present study was to evaluate the correlation between the proportional change of anteroposterior diameter (APD) of levator hiatus from rest to maximum Valsalva maneuver in nulliparous women at term and labor outcome. Methods: We prospectively recruited nulliparous women at term before the onset of labor. Women underwent a two-dimensional transperineal ultrasound, measuring the APD of the levator hiatus at rest and under maximum Valsalva's maneuver. APD change from rest to maximum Valsalva was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 37 publications
(94 reference statements)
0
14
0
Order By: Relevance
“…Other authors examined the correlation between APD obtained by 2D TPUS at term before the onset of labor and the mode of delivery 20,21,25,26 . Kamel et al included a group of nulliparous women undergoing induction of labor 21 .…”
Section: Pelvic Floor Dimensions and The Mode Of Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors examined the correlation between APD obtained by 2D TPUS at term before the onset of labor and the mode of delivery 20,21,25,26 . Kamel et al included a group of nulliparous women undergoing induction of labor 21 .…”
Section: Pelvic Floor Dimensions and The Mode Of Deliverymentioning
confidence: 99%
“…Similarly, Youssef et al did not find a correlation between any of APD measurements at term and the incidence of Cesarean delivery in a group of nulliparous women at term 26 . Recently, Brunelli et al assessed the role of a change in APD with maternal pushing at term before the onset of labor and labor outcome 20 . In their large cohort of 486 nulliparous women, the change in APD from rest to Valsalva did not correlate with the risk of operative delivery (Cesarean or instrumental).…”
Section: Pelvic Floor Dimensions and The Mode Of Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…83 Levator hiatus can also be used reliably with volumetric transperineal ultrasound assessment. 84 The levator hiatus can be measured on the axial plane of a three-dimensional acquired volume of the pelvic floor (Figure 8).…”
Section: Assessment Of Pelvic Floor Dimensions and Functionmentioning
confidence: 99%
“…Several studies have found a correlation between pelvic floor dimensions, levator ani muscle coactivation at term, and the outcome of labor . [41][42][43] Youssef et al 44 reported the clinical impact of ultrasound evidenced levator ani coactivation and outcome of labor. As levator ani muscle coactivation can be recognized during late pregnancy, the authors concluded that this might be an opportunity to help women to improve their pelvic floor relaxation before the onset of labor.…”
Section: -11mentioning
confidence: 99%